2011
DOI: 10.1186/1758-5996-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Progression to microalbuminuria in patients with type 1 diabetes: a seven-year prospective study

Abstract: BackgroundThe presence of microalbuminuria can be associated with overt nephropathy and cardiovascular disease in patients with type 1 diabetes (T1D). We aimed to determine the incidence and evaluate the baseline predictors for the development of microalbuminuria in patients with T1D.MethodsThis study is a longitudinal cohort study of 122 normoalbuminuric patients with T1D who were receiving routine clinical care at baseline. A detailed medical history was taken, and a physical examination was performed at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
4
3
0
Order By: Relevance
“…Although most of the studied patients achieved the sBP, dBP and HDL cholesterol goals, 30 to 50% did not reach the goals for triglycerides, LDL cholesterol and non-HDL cholesterol levels, which was similar to the data found in other observational studies [7,18,28-30]. Although there is a slight prevalence of patients that have reached BMI levels resembling Brazilian overweight/obesity statistics [31], the present results suggested an additional major health issue in T1D patients in all geographic regions is overweight or obese patients, which was similar to results found in other populations with T1D [7,18,32,33] and in patients with T2D in Brazil [9]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although most of the studied patients achieved the sBP, dBP and HDL cholesterol goals, 30 to 50% did not reach the goals for triglycerides, LDL cholesterol and non-HDL cholesterol levels, which was similar to the data found in other observational studies [7,18,28-30]. Although there is a slight prevalence of patients that have reached BMI levels resembling Brazilian overweight/obesity statistics [31], the present results suggested an additional major health issue in T1D patients in all geographic regions is overweight or obese patients, which was similar to results found in other populations with T1D [7,18,32,33] and in patients with T2D in Brazil [9]. …”
Section: Discussionsupporting
confidence: 91%
“…With regard to T1D patients who were above their goal, one study at academic medical centers observed a low rate of medication management [8]. Considering overweight, obesity, hypertension and dyslipidemia as CV risk factors, it can be concluded that the young patients in the present study represent a high-risk group for microvascular and macrovascular complications of diabetes, as described in other studies [30,32,33]. Although a high number of current smokers were noted in the south region in the present study, there were fewer T1D patients who were current smokers than previously reported in Europe [18] and USA [34].…”
Section: Discussionsupporting
confidence: 71%
“…There is compelling evidence that intensive management of weight, cholesterol and blood pressure is effective in delaying or preventing microvascular and macrovascular complications. Although most of our patients reached the sBP and total cholesterol goals, 40-50% did not reach the dBP, LDL cholesterol, HDL cholesterol or non-HDL cholesterol goals, which is similar to the data found in other observational studies [7,18,23,24,27]. However, our results suggest that an additional major health issue in T1DM is being overweight or obese, similar to results found in other populations with T1DM [7,18,25,26] and in patients with T2DM in Brazil [9].…”
Section: Discussionsupporting
confidence: 90%
“…Diabetes is a group of metabolic diseases characterized by a sustained increase of high blood glucose levels over a prolonged period, acting as one of the leading causes of morbidity and mortality worldwide; type 1 diabetes (T1D) and type 2 diabetes (T2D) are the two major types ( 1 ). Diabetic nephropathy (DN) is estimated to be one of the major serious chronic complications in patients with diabetes, affecting approximately one third of people with T1D or T2D ( 2 ). The rising tide of DN may be greatly associated with the dramatically increasing rate of diabetes population currently, with concomitant increase in associated cardiovascular mortality and end-stage renal disease, producing significant social and economic ramifications in the developing world particularly ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%